Letter from Émile Wangermeé, vice governor-general of Belgian Congo, to Roger Casement, written in French, thanking him for attending the celebration of the seventeenth anniversary of the proclamation of the founding of the state, - Wangermeé, Émile, 1855-1924 (1902)
Letter furthermore includes annotated note by Arthur Nightingale stating the letter is a true and faithful copy of the original, and is dated as April 20th 1904.